2003
DOI: 10.1111/j.1523-1739.2003.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Cattle Grazing Impacts on Annual Forbs and Vegetation Composition of Mesic Grasslands in California

Abstract: Livestock grazing represents a major human alteration of natural disturbance regimes in grasslands throughout the world, and its impacts on plant communities have been highly debated. We investigated the impact of cattle grazing on the California coastal prairie plant community with a focus on native annual forbs, a number of which are of conservation concern. In spring 2000 and 2001, we surveyed the vegetation community composition, vegetation structure, and soil chemical parameters at 25 paired grazed and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
180
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(206 citation statements)
references
References 48 publications
19
180
4
3
Order By: Relevance
“…Prescribed fire and grazing are among the mostoften applied management strategies in grassland ecosystems for the purposes of restoration of native biodiversity (Bakker 1989;Hayes and Holl 2003;Corbin et al 2004;Huntsinger et al 2007;Reiner 2007). Often, such treatments are specifically timed to take advantage of the earlier growth and flowering time of the exotic annual species compared to the native perennials-e.g., grazing in March rather than June (Love 1944;Huntsinger et al 2007).…”
Section: Implications For Controlmentioning
confidence: 99%
“…Prescribed fire and grazing are among the mostoften applied management strategies in grassland ecosystems for the purposes of restoration of native biodiversity (Bakker 1989;Hayes and Holl 2003;Corbin et al 2004;Huntsinger et al 2007;Reiner 2007). Often, such treatments are specifically timed to take advantage of the earlier growth and flowering time of the exotic annual species compared to the native perennials-e.g., grazing in March rather than June (Love 1944;Huntsinger et al 2007).…”
Section: Implications For Controlmentioning
confidence: 99%
“…More recently, however the number of livestock is increasingly oversized (Yang, 1999). Excessive grazing can affect not only the community structure of vegetation, influencing microhabitat selection and thermoregulatory behavior during terrestrial migration of frogs (Kiehl et al, 1996;Eccard et al, 2000;Hayes and Holl, 2003) but also threaten small waterbodies used for reproduction and overwintering by R. kukunoris through the actions of trampling and erosion (YQ, pers. obs.).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have consistently demonstrated that properly timed (late-spring, post-bolting/preflowering phenological stages -that is, immediately prior to seed head production) and intensive (high animal density resulting in high pressure on vegetation) grazing can reduce medusahead cover by 30% to 100% and yellow starthistle flower heads by 75% to 90% (DiTomaso et al 2008;Thomsen et al 1993). Experimentally manipulated livestock grazing has also been shown to enhance herbaceous diversity and native plant richness in vernal pools, interior annual grasslands and coastal grassland sites (DiTomaso et al 2008;Hayes and Holl 2003;Marty et al 2005). However, there is little published work examining pasture-scale (greater than 80 acres) implementation of prescribed grazing to manage invasive weeds.…”
Section: Managing Weeds With Grazingmentioning
confidence: 99%